Pengaruh Loyalitas Pelanggan Melalui Penerapan Harga, Switching Barrier Dan Trust In Brand - Mega Wulan; Rita Tri Yusnita; Depy Muhamad Pauzy (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine the Effect of Price on Switching Barrier, Trust in brand on Switching Barrier and to determine the Effect of Price, Switching Barrier and Trust in Brand on Customer Loyalty (Survey on customers of PT. Sinar Niaga Sejahtera Garudafood Depo Tasikmalaya Distribution Division). The method used in this research is quantitative method, the research sample is 80 respondents and the analytical tool used in this research is path analysis using SPSS version 25. The method of determining the sample uses probability sampling. The results of this study indicate that the price has a significant effect on the Switching Barrier; Trust in Brand has a significant effect on Switching Barrier; Price, Switching Barrier and Trust in Brand simultaneously have a significant effect on Customer Loyalty; Price partially has no significant effect on customer loyalty; Switching Barrier partially has a significant effect on Customer Loyalty; Trust in Brand partially has a significant effect on Customer Loyalty; Price through Switching Barrier has a significant effect on Customer Loyalty; Trust in Brand through Switching Barrier has no significant effect on Customer Loyalty.